I will surprise my friend! - Willems, Mo. (New York : Hyperion Books for Children, an imprint of Disney Book Group, 2008)
Gerald the elephant and Piggie, who are best friends, play a game to surprise each other by a big rock and their fun takes a strange turn when Gerald gets worried.
0.8
K-3.
K-3
Keywords: Friendship -- Juvenile fiction; Games -- Juvenile fiction; Friendship -- Fiction; Games -- Fiction; Friendship -- Fiction; Games -- Fiction; Humorous fiction; Readers (Publications)